Poor 1-year outcomes following percutaneous coronary interventions in systemic lupus erythematosus: Report from the National Heart, Lung and Blood Institute Dynamic Registry - Maksimowicz-McKinnon, Kathleen (2008)
BACKGROUND: Women with systemic lupus erythematosus (SLE) have premature and accelerated atherosclerosis. Although percutaneous coronary intervention (PCI) is utilized frequently to treat coronary artery disease (CAD) in SLE, little is known regarding PCI outcomes immediately post-PCI and after discharge. METHODS AND RESULTS: Baseline demographic, procedure-related and adverse outcome data on consecutive patients undergoing PCI during 5 recruitment “waves” of the National Heart, Lung, and Blood Institute Dynamic Registry across 23 clinical centers were collected. SLE patients (n= 28) were compared to nonSLE patients (n=3385). SLE patients were younger and more often female in comparison to nonSLE patients undergoing PCI. SLE patients were less likely than nonSLE patients to have hyperlipidemia, but had a similar prevalence of hypertension, diabetes mellitus, and tobacco use. The prevalence of multi-vessel disease was similar between groups. Initial intervention success (by angiographic definition) was not significantly different between groups. At one year, SLE patients were more likely to suffer a myocardial infarction (MI) (15.6% vs. 4.8%, p=0.01), and more often required repeat PCI (31.3% vs. 11.8%, p=0.009) than nonSLE patients, even following adjustment for important covariates. CONCLUSIONS: SLE patients had significantly worse CV outcomes at one year than nonSLE patients. Even considering the small number of SLE patients, these differences were striking. Further study is warranted to explore other factors potentially accounting for this disparity, including SLE disease activity and duration, presence of hypercoagulable state, and immunosuppressive therapy.